2016
DOI: 10.1186/s12939-016-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Equity of access to primary healthcare for vulnerable populations: the IMPACT international online survey of innovations

Abstract: BackgroundImproving access to primary healthcare (PHC) for vulnerable populations is important for achieving health equity, yet this remains challenging. Evidence of effective interventions is rather limited and fragmented. We need to identify innovative ways to improve access to PHC for vulnerable populations, and to clarify which elements of health systems, organisations or services (supply-side dimensions of access) and abilities of patients or populations (demand-side dimensions of access) need to be stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 33 publications
5
123
1
5
Order By: Relevance
“…Richard et al [54] suggested developing co-operative and participatory initiatives to achieve these goals. In this research we sought to do just that - using participatory methods to include the views of a variety marginalised patients on the factors influencing their access to health services.…”
Section: Introductionmentioning
confidence: 99%
“…Richard et al [54] suggested developing co-operative and participatory initiatives to achieve these goals. In this research we sought to do just that - using participatory methods to include the views of a variety marginalised patients on the factors influencing their access to health services.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who had less formal education are normally associated with a lower income, which probably hinders access to dental care services since less financial resources are available for dental treatment and periodic consultations with dentists. Literature highlights that socioeconomic conditions are directly related to the frequency of recent consultations with dentists [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…As inequalities regarding access and utilization of health services have been identified, it is important to elaborate strategies and actions that improve access possible for people with lower income to public dental care services. Although innovative initiatives have been proposed, the inequalities do not present a decreasing rate over time 19,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, the necessary changes can be initiated neither in organization of health services nor in enhancing ability of Roma to use properly the health services [7]. Moreover, this problem hindering the elaboration of targeted interventions is reflected in the restricted effectiveness of programmes that aim at improvement of the health status of Roma people in European countries with significant Roma minorities.…”
Section: Of 15mentioning
confidence: 99%
“…Using these indicators, improvement in the effectiveness of the Roma projects is expected. The necessity of this kind of monitoring technology has been emphasized by the EU, the WHO, and national authorities, as well [5][6][7]10, 23].…”
Section: New Indicator Set For Segregated Roma Settlementsmentioning
confidence: 99%